Kaidah Al-Masyaqqah Tajlib Al-Taysir: Kajian Komprehensif tentang Kesulitan, Rukhshah, dan Cabang-Cabangnya dalam Fiqih Islam - Halimah Halimah; Gita Anggraini; Azh-Zhahra Olfa; Desvyna Tri Yanitha; Lahmudinur Lahmudinur (Student Research Journal, 2026)
This study discusses the rules of al-masyaqqah tajlibu at-taysir as one of the rules of asasiyyah fiqhiyyah which has an important role in the formation and application of Islamic law. This rule emphasizes that the difficulties (masyaqqah) experienced by the mukallaf can be the reason for the provision of convenience (taysir) in the implementation of sharia law. This research aims to explain the concept of masyaqqah, the legal basis of the rules, the forms of rukhsah given by the sharia, and the limitations and exceptions of its application. The research method uses literature studies by analyzing fiqh literature, ushul fiqh, and relevant Islamic law sources. The results of the study show that the masyaqqah that can be the basis for legal leniency is not ordinary difficulties in worship and muamalah, but difficulties that exceed normal limits and have the potential to cause harm. The basis of this rule is found in the Qur'an and Hadith, which affirm that Allah desires ease and does not desire difficulties for His servants. In its application, masyaqqah is classified into three levels: light, medium, and severe, with different legal consequences. The forms of rukhsah include mandatory, sunnah, mubah, khilaf al-aula, and makruh according to the conditions. However, the application of this rule is not absolute because there are limits to remain in harmony with maqashid al-shari'ah. Thus, this rule is an important instrument in maintaining a balance between the demands of sharia and human capabilities.